Arts and cultural leadership : creating sustainable arts organizations. - Foster, Kenneth J. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This textbook provides an expert overview of the challenge of arts and cultural leadership in the contemporary world. Grounded in theories of sustainability and with a renewed global focus for this second edition, the author's insights from contemporary arts organizations facilitate meaningful student comprehension. Drawing on the work of practitioners and theorists in the fields of philosophy, biology, and ecology as well as the arts, Foster proposes a rethinking of organizational design, strategy, and structure that is based on ecological concepts and the creative process that is intrinsic to the arts rather than the conventional business model that currently prevails, particularly in western arts and culture organizations. He contests conventional thinking about arts administration and management and urges arts leaders to foreground innovation as they reimagine their organizations for a world unlike any other. New sections include an enhanced theoretical discussion as well as new material on business models, strategy, and organizational design and practice. Applicable to any arts organization, the entrepreneurial focus is especially relevant in the aftermath of the global pandemic, the ongoing climate crisis, and the quest for democracy and social justice. This updated edition will be a valuable resource both for present-day arts and cultural leaders who are working to adapt to the current environment as well as students and future leaders who aspire to make change in the world through arts and cultural leadership.
OCLC-licensed vendor bibliographic record.
Keywords: Performing arts -- Management; Organizational change; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Industries -- Service Industries